Wuthering heights - Brontë, Emily (Puffin classics; London, 2009)
In early nineteenth-century Yorkshire, the passionate attachment between a headstrong young girl and a foundling boy brought up by her father causes disaster for them and many others, even in the next generation. Includes explanatory notes throughout the text, an introduction discussing the author and the background of the story, and a study guide